Phase transitions in multicomponent media at low temperatures - Chernobai, Nadiia; Vozovyk, Krystyna; Kadnikova, Nataliya (Problems of Cryobiology and Cryomedicine, 30(3), 294, 2020)
In cryobiological techniques for microalgal cryopreser-vation, the culture media are most commonly used as the basic solutions. The processes, occurring in these solutions when temperature decreases signifi cantly contribute into suc-cessful cryopreservation and the culture preservation after freeze-thawing. However, the reported data on the kinetics of phase transitions and eutectic temperatures for multicom-ponent media with diff erent degrees of mineralization, used in microalgal cultivation, are insuffi cient.
Фазові переходи в багатокомпонентних середовищах за низьких температур
Vozovik , K., Chernobai , N., & Kadnikova, N. (2020). Phase Transitions in Multicomponent Media at Low Temperatures. Problems of Cryobiology and Cryomedicine, 30(3), 294. https://doi.org/10.15407/cryo30.03a.294
Keywords: Low Temperatures; Phase Transitions; microalgae; cryopreservation